2004
DOI: 10.1111/j.1600-0609.2004.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly progressive diffuse large B‐cell lymphoma with initial clinical presentation mimicking seronegative Wegener's granulomatosis

Abstract: Here we present a 40-yr-old male patient with an aggressive B-cell lymphoma, who presented 2 yr earlier with polyarthritis, and was responsive to steroids and oral methotrexate. Thereafter he developed skin and lung lesions which on biopsy consisted of mixed 'inflammatory' infiltrates with granulomatous vasculitis. A diagnosis of seronegative Wegener's granulomatosis was made and the patient received a combination of prednisone and cyclophosphamide with clinical improvement and clearance of the radiological le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
4
1
1
Order By: Relevance
“…Although similar observation was reported in some literature, these three cases were concluded to be pulmonary disease with cavitation mimicking Wegener's granulomatosis [15][16][17]. What differed from our case was that these reports were described for young adult cases (from 27 to 40 years old) with disease of nasal and/or renal mucosa.…”
Section: Discussioncontrasting
confidence: 64%
“…Although similar observation was reported in some literature, these three cases were concluded to be pulmonary disease with cavitation mimicking Wegener's granulomatosis [15][16][17]. What differed from our case was that these reports were described for young adult cases (from 27 to 40 years old) with disease of nasal and/or renal mucosa.…”
Section: Discussioncontrasting
confidence: 64%
“…Miyahara et al [11] reported a patient with a pulmonary cavitary mass, who was first misdiagnosed with GPA with transbronchial biopsy and then diagnosed as diffuse large B-cell lymphoma with open biopsy. Cohen et al [12] reported a patient who presented and was treated for seronegative GPA, and FNAB of the lung lesion of the patient was consistent with GPA. The patient was then diagnosed with rapidly progressive diffuse large B-cell lymphoma with biopsy, and it was thought that treating non-malignant diseases with immunosuppressive agents might lead to the development of chemoresistant lymphoma.…”
Section: Resultsmentioning
confidence: 91%
“…Frequently, the origin of primary extranodal NHLs can be ascribed to one given organ system or site, with the most common extranodal sites represented by the stomach, skin (Kadin & Carpenter, 2003; Hsi, 2004), and small intestine; also breast (Grubstein et al. , 2005), thyroid (Widder & Pasieka, 2004), lung (Cohen et al. , 2004), heart (Chalabreysse et al.…”
Section: Introductionmentioning
confidence: 99%
“…The overall percentage of NHLs coded as being of extranodal origin is between 25% and 35% in most countries. Frequently, the origin of primary extranodal NHLs can be ascribed to one given organ system or site, with the most common extranodal sites represented by the stomach, skin (Kadin & Carpenter, 2003;Hsi, 2004), and small intestine; also breast (Grubstein et al, 2005), thyroid (Widder & Pasieka, 2004), lung (Cohen et al, 2004), heart (Chalabreysse et al, 2002), liver (Eom et al, 2004), genitourinary tract (Kirk et al, 2001;Novella et al, 2001;Kahlifa, Buckstein & Perez-Ordonez, 2003; Khaitan et al, 2004;Heredia et al, 2005;Yildirim, 2005), adrenals (Singh et al, 2004) and bone could primarily affected. However, a heterogeneous group of NHLs, including DLBCL, Burkitt's lymphoma, and mucosa-associated lymphoma tissue (MALT) lymphoma, involves multiple extranodal sites at presentation (Economopoulos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%